Pembelajaran Aljabar Melalui PMRI Berbantu Permainan Kelereng Pada Siswa Kelas 3 SD 3 Sidigede - Sofiyani Sofiyani; Tiara Noor Rohmah; Eka Zuliana (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
This research aims to analyze Algebra learning by applying the principles of PMRI (Indonesian Realistic Mathematics Education) through the game of marbles at SD 3 Sidigede, especially in class 3. The research method used is using a qualitative approach, namely describing the process of playing the game and the benefits of playing marbles. The subjects in this research were grade 3 students at SD 3 Sidigede where the number of students in one class was 30 people consisting of 10 boys and 20 girls. The results of this research are that the ability to learn algebra in this class is good. Students can perform addition and subtraction operations on a pattern presented containing predetermined numbers. In this learning, the principles of PMRI (Indonesian Realistic Mathematics Education) have been applied, namely in a marble game. Where the game of marbles can train students' motor skills, train their thinking skills, their ability to count, sharpen their social skills and can train children to control their emotions.